Ken grew 0.425 of an inch more than sang.
Arithmetic operations can also be specified by subtracting, dividing, and multiplying built-in functions. The operator that performs the arithmetic operation is called the arithmetic operator.
Operators which let do a basic mathematical calculation
+ Addition operation: Adds values on either side of the operator.
For example 12 + 2 = 14
- Subtraction operation: Subtracts the right-hand operand from the left-hand operand.
for example 12 -2 = 10
* Multiplication operation: Multiplies values on either side of the operator
For example 12*2 = 24
Given that ken grew 4/5 of an inch last year
And Sang grew 3/8 of an inch
Converting the fraction into decimals
⇒ 3/8 = 0.375
⇒ 4/5 = 0.8
ken grew 0.375 of an inch last year
And Sang grew 0.8 of an inch
Take those two figures and subtract the smaller amount from the larger number.
⇒ 0.8 - 0.375
⇒ 0.425
So, ken grew 0.425 of an inch more than sang
Hence, ken grew 0.425 of an inch more than sang
Learn more about Arithmeticoperations here:
#SPJ2
The pairs of numbers that multiply to 90 are (1, 90), (2, 45), (3, 30), (5, 18), (6, 15), and (9, 10).
To find two numbers that multiply to equal 90, we can look for pairs of factors of 90.
The factors of 90 are: 1, 2, 3, 5, 6, 9, 10, 15, 18, 30, 45, and 90.
To determine the pairs of factors that multiply to 90, we can list the pairs:
1 × 90 = 90
2× 45 = 90
3 × 30 = 90
5 × 18 = 90
6 × 15 = 90
9 × 10 = 90
Therefore, the pairs of numbers that multiply to 90 are: (1, 90), (2, 45), (3, 30), (5, 18), (6, 15), and (9, 10).
To learn more on Multiplication click:
#SPJ6
A 143 divided by 11 equals 13.
To calculate 143 divided by 11 using long division, follow these steps:
To know more about divided:
#SPJ6
-6+{14+2 [60 – 9(1+3)]}
Enter your answer in the box.
Answer:
56
Step-by-step explanation:
To simplify the given expression, solve the innermost parentheses first, followed by simplifying the expression within the brackets, and finally performing addition. The simplified expression is 56.
To simplify the given expression, we need to follow the order of operations (PEMDAS/BODMAS). In the given expression, we start by solving the innermost parentheses first:
9(1+3) = 9(4) = 36.
Then, we simplify the expression inside the brackets:
[60 - 36] = 24.
Finally, we substitute the value of the simplified expression back into the original expression:
-6 + {14 + 2 × 24} = -6 + {14 + 48}.
Further simplification within the brackets:
-6 + {62}.
And finally, performing the addition:
-6 + 62 = 56.
Therefore, the simplified expression is 56.
#SPJ2
set up your equation
Length x Width x Height = Volume
plug in the known factors and simplify L x W x H. Divided the numerical value on both sides. you are left with H